SUPREMASI HUKUM DALAM MEKANISME IMPEACHMENT BERDASARKAN UUD 1945 - Hermayanti Hermayanti (Jurnal LEX SPECIALIS, 2012)
Abstract One component of the establishment of the rule of law in the State under the law determined by the substance of the law itself. In the sense that the substance of the law should include arrangements to ensure that the law which supreme. In connection with that, the mechanism of impeachment against the president and / or vice president by the 1945 Constitution many people do not fully guaranteeing the rule of law, is this so? This paper attempts to discuss particular aspects of the legal substance of the impeachment mechanism Key Note : Rule of Law, Substance Law, Impeachment